Experiences Using New Zealand’s Hospital Based Surveillance System for Injury Prevention Research - Langley, J. D. (Methods of Information in Medicine, 1995)
The focus of this paper is the Injury Prevention Research Unit’s (IPRU’s) experience in analysing New Zealand’s national inpatient public hospital injury data set. The existence of the national inpatient data management system has enabled the IPRU to develop an injury morbidity data set for the period of 1979-1992. The IPRU, thus, has data on over 250,000 injury events that were serious enough to warrant admission to a hospital. This data set has been used extensively by the IPRU to address a wide range of injury issues from demographic, environment, activity, product, and injury perspectives. Apart from the demographic variables, those variables that have proved most useful in our work have been: length of stay, readmission indicator, a personal identifier code number, WHO International Classification of Disease coding for diagnoses and external cause of injury (E-code), and written descriptions of external cause of injuries and location of injury event. Practical examples of IPRU’s use of each of these variables are given. These examples demonstrate how invaluable New Zealand’s inpatient injury data set is for documenting resource utilisation, accurately determining the incidence of events, undertaking analytical epidemiological studies including evaluations, and addressing shortcomings in E-codes. A key aspect of the system is the narrative information. Evidence is produced demonstrates that the electronic recording of narratives of the circumstances of injury is an invaluable tool for conducting epidemiological research which has direct implications for injury prevention policy and practice. Given the numerous objections that are raised about E-coding, injury prevention personnel would be well served to encourage health authorities to electronically record narratives as a first step towards uniform coding.
Keywords: Injury; Surveillance; Prevention; Hospital; Inpatient